2021
DOI: 10.5194/bg-18-6517-2021
|View full text |Cite
|
Sign up to set email alerts
|

Strong temporal variation in treefall and branchfall rates in a tropical forest is related to extreme rainfall: results from 5 years of monthly drone data for a 50 ha plot

Abstract: Abstract. A mechanistic understanding of how tropical-tree mortality responds to climate variation is urgently needed to predict how tropical-forest carbon pools will respond to anthropogenic global change, which is altering the frequency and intensity of storms, droughts, and other climate extremes in tropical forests. We used 5 years of approximately monthly drone-acquired RGB (red–green–blue) imagery for 50 ha of mature tropical forest on Barro Colorado Island, Panama, to quantify spatial structure; tempora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 58 publications
8
38
0
Order By: Relevance
“…Previous studies have shown that mortality rates are important for variation in standing biomass regionally and globally; we show that the same is true on a landscape scale for mature tropical forest and identify abiotic variables that control this variation. Our average canopy disturbance rates across BCI, 1.8% yr −1 to 2.1% yr −1 , are comparable to estimates of woody mortality fluxes on BCI (Meakem et al, 2018; 1.9% yr −1 of total live biomass) and disturbance rates in a previous study using higher resolution drone imagery over the 50 ha plot (Araujo et al, 2021; ~2.2% yr −1 ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previous studies have shown that mortality rates are important for variation in standing biomass regionally and globally; we show that the same is true on a landscape scale for mature tropical forest and identify abiotic variables that control this variation. Our average canopy disturbance rates across BCI, 1.8% yr −1 to 2.1% yr −1 , are comparable to estimates of woody mortality fluxes on BCI (Meakem et al, 2018; 1.9% yr −1 of total live biomass) and disturbance rates in a previous study using higher resolution drone imagery over the 50 ha plot (Araujo et al, 2021; ~2.2% yr −1 ).…”
Section: Discussionsupporting
confidence: 86%
“…In general, forces from wind are the proximate cause of most treefalls (Gardiner, 2021), although preconditions such as heartrot and lighting damage can contribute to susceptibility to wind, and saturated soils can increase uprooting risk. Disturbance rates on BCI are highest in wet season periods with extreme precipitation, consistent with the idea that storm‐associated winds and soil saturation contribute to canopy disturbance in this landscape (Araujo et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Repetitive UAV surveys of the same area were designed to collect time series as a database for change analysis. Hence, the scientists analyzed spectral and structural changes over time to assess mechanical crown damage [97,98], fire damage based on pre-and postfire data [99][100][101], phenological differences [89], and different stages of stress-induced symptoms evident in the tree canopy [92,94,[102][103][104][105][106][107][108][109][110][111][112]. The primary period of FHM typically lay within the growing season.…”
mentioning
confidence: 99%